2019
DOI: 10.1002/ar.24264
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Alpinumisoflavone Inhibits Tumor Growth and Metastasis in Papillary Thyroid Cancer via Upregulating miR‐141‐3p

Abstract: Alpinumisoflavone (AIF) as a principal active ingredient of traditional Chinese herb Derris eriocarpa exerts a broad spectrum of anticancer activities against solid tumors. However, little is known about the effect of AIF on papillary thyroid cancer (PTC). Objectives of this study are to investigate the effect of AIF on cell growth, apoptosis, and metastasis of PTC cells and uncover its underlying mechanisms. Results showed that AIF treatment notably suppressed cell viability, migration, invasion, and epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…A number of flavonoid compounds have been reported to enhance the sensitivity of ESCC to chemotherapy or radiotherapy. As one of the most active ingredients of Derris Eriocarpa, AIF showed antiapoptosis effect in a variety of human malignancies including ESCC (Fang et al, 2019; Gao, Chang, Wang, Ban, & Zhang, 2017; Han et al, 2016; Li et al, 2019; Wang et al, 2017; Zhao, Zhang, Jiang, & Gao, 2019). We found that AIF was capable to increase the radiation sensitivity of ESCC cells, which was also validated in in vivo study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of flavonoid compounds have been reported to enhance the sensitivity of ESCC to chemotherapy or radiotherapy. As one of the most active ingredients of Derris Eriocarpa, AIF showed antiapoptosis effect in a variety of human malignancies including ESCC (Fang et al, 2019; Gao, Chang, Wang, Ban, & Zhang, 2017; Han et al, 2016; Li et al, 2019; Wang et al, 2017; Zhao, Zhang, Jiang, & Gao, 2019). We found that AIF was capable to increase the radiation sensitivity of ESCC cells, which was also validated in in vivo study.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse pharmacological activities of AIF including atheroprotective (Ateba et al, 2019), estrogenic (Mvondo, Njamen, Tanee Fomum, & Wandji, 2012), and antibacterial (Chukwujekwu, Van Heerden, & Van Staden, 2011) have been reported. Furthermore, the role of AIF as a potential antineoplastic agent has also been reported (Fang, Liu, Liu, & Qian, 2019). Our previous work also showed that AIF could increase the sensitivity of ESCC cells to irradiation (Zhang, Fan, Wang, Zhu, & Li, 2017).…”
Section: Introductionmentioning
confidence: 91%
“…The luciferase reporter assay further verified our speculation that miR-141-3p is a target of ZEB1-AS1. MiR-141-3p is a novel miRNA involved in cancer [35][36][37]. Recently studies showed that miR-141-3p might participate in the progression of CRC by directly targeting EGFR [38], TRAF5 [39] and ZEB1 [40].…”
Section: Discussionmentioning
confidence: 99%
“…Genistein and daidzein are the most studied compounds of this subgroup in terms of medical applications. Nevertheless, other isoflavones such as glabridin and alpinumisoflavone have raised interest as potential cancer medicines in various types of cancer such as breast, liver, or thyroid cancers [ 131 , 132 ].…”
Section: Polyphenolsmentioning
confidence: 99%